2014
DOI: 10.1103/physrevd.89.053009
|View full text |Cite
|
Sign up to set email alerts
|

Two-zero Majorana textures in the light of the Planck results

Abstract: The recent results of the Planck experiment put a stringent constraint on the sum of the light neutrino masses, Σ i m i < 0.23 eV (95% CL). On the other hand, two-zero Majorana mass matrix textures predict strong correlations among the atmospheric angle sin 2 θ 23 and Σ. We use the Planck result to show that, for the normal hierarchy case, the texture with vanishing (2, 2) and (3, 3) elements is ruled out at a high confidence level; in addition, we emphasize that a future measurement of the octant of θ 23 (or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 31 publications
9
70
0
Order By: Relevance
“…Our results for the textures P 3 and P 4 are compatible with ones [18][19][20][21][22][23][24][25], obtained before. Now we turn to the analysis of the one texture zero neutrino mass matrices we have obtained in Section 3.…”
Section: Predictions From P 1234 Type Neutrino Mass Matricessupporting
confidence: 81%
See 1 more Smart Citation
“…Our results for the textures P 3 and P 4 are compatible with ones [18][19][20][21][22][23][24][25], obtained before. Now we turn to the analysis of the one texture zero neutrino mass matrices we have obtained in Section 3.…”
Section: Predictions From P 1234 Type Neutrino Mass Matricessupporting
confidence: 81%
“…Dirac Yukawa couplings and heavy Majorana neutrino masses) which are not measured so far, a priory it is impossible to make predictions unless some reduction of model parameters are achieved. For this purpose, the texture zero Yukawa and/or Majorana mass matrices have been investigated in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. This approach, besides some predictions, opens up a possibility of relating phase δ (appearing in neutrino oscillations) to the CP asymmetry of the thermal leptogenesis [14][15][16], [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is a combination of two very different approaches to lepton flavor: (a) texture-zeros that increase predictivity and relate mixing angles with masses [26][27][28][29][30] and (b) symmetries that fully or partly determine the mixing structure independently of the masses [10,11,31]. The former usually requires abelian symmetries [32] while the latter requires nonabelian discrete symmetries [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…According to Dev et al 55 and Meloni et al, 56 we employ the values of θ 23 given for both octant which are shown in TABLE 1.…”
Section: 2017 1:25 Wspc/instruction File Kitabayashi˙ohkawa˙yasue˙mentioning
confidence: 99%
“…[55][56][57][58] This type of matrix is called the two zero flavor neutrino mass texture. If we require a nonvanishing effective neutrino mass M ee for the neutrino less double beta decay, 59,60 only four textures are compatible with observed data in the two zero flavor neutrino mass texture scheme.…”
mentioning
confidence: 99%